2004
DOI: 10.1007/s11243-004-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new octakis(benzylthio)tetraazaporphyrin complexes with bivalent transition metal ions and an investigation of their spectral, redox and catalytic properties

Abstract: Transition metals in the þ2 oxidation state form complexes with octakis(benzylthio)tetraazaporphyrin [M{TAP(SBn) 8 }] (M ¼ Mn 2þ , Co 2þ , Ni 2þ , Cu 2þ , Zn 2þ and 2H þ ; Bn ¼ ACH 2 Ph; TAP ¼ tetraazaporphyrin) and were prepared via demetallation of the template-synthesized complex [Mg{TAP(SBn) 8 }] in ClCH 2 COOH, followed by insertion of the metal ions in a PhCl-DMF mixture. All compounds were characterized by u.v-vis, 1 H-n.m.r., e.s.r. and mass spectra, microanalyses and magnetic susceptibility data. PM3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…The pentanuclear complexes generally exhibited good voltammograms, with multiple oxidation waves, as compared with corresponding dinuclear complexes. Since nickel(II) porphyrin exhibits an irreversible oxidation at E p = 1.2 V vs SCE in DMF [57], considering the relative peak currents and in analogy with our earlier studies, the lower oxidation wave at E 1/2 = 0.39 V could be assigned to the Ru II /Ru III process, while the other two waves at E 1/2 = 0.68 and 0.91 V could be attributed to the two successive oxidations of the [Ni(OBTTAP)] [28,[58][59][60][61]. The Ru II /Ru III process at E 1/2 = 0.38 V as compared to that observed in the [(bpy) 2 Ru-{S 2 Bn 2 C 2 (CN) 2 ] 2+ (E 1/2 = 1.04 V), is very much easier.…”
Section: Cyclic Voltammetrysupporting
confidence: 86%
See 1 more Smart Citation
“…The pentanuclear complexes generally exhibited good voltammograms, with multiple oxidation waves, as compared with corresponding dinuclear complexes. Since nickel(II) porphyrin exhibits an irreversible oxidation at E p = 1.2 V vs SCE in DMF [57], considering the relative peak currents and in analogy with our earlier studies, the lower oxidation wave at E 1/2 = 0.39 V could be assigned to the Ru II /Ru III process, while the other two waves at E 1/2 = 0.68 and 0.91 V could be attributed to the two successive oxidations of the [Ni(OBTTAP)] [28,[58][59][60][61]. The Ru II /Ru III process at E 1/2 = 0.38 V as compared to that observed in the [(bpy) 2 Ru-{S 2 Bn 2 C 2 (CN) 2 ] 2+ (E 1/2 = 1.04 V), is very much easier.…”
Section: Cyclic Voltammetrysupporting
confidence: 86%
“…Q and Soret bands (Table 1). In complex 1 the Q band was observed at 627 nm and the Soret band at 320 nm [28]. The latter band is nearly three times more intense than the former one.…”
Section: Electronic Spectramentioning
confidence: 88%
“…At the same time, the substrates with electron‐withdrawing groups such as ‐NO 2 (entry 3) and ‐Br (entry 4) needed longer reaction time than those with electron‐donating groups such as ‐CH 3 , ‐OCH 3 (entry 6 and 2) to obtain satisfied yields. In particular Benzil, which were used as building blocks for the synthesis of pharmaceuticals, photo initiators and precursors of porphyrins, are also obtained from benzoin in high yield after 3 h. It indicated that the position of substituentof benzyl alcohols has little effect on the oxidation, but higher electron density and conjugation effect on α‐carbon with hydroxyl group is favorable to this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Porphyrinic macrocycles have aroused renewed research interest for its potential for creating structure diversity since the inherent synthesis ease of diverse peripheral substituents . Recently, metal phthalocyanine (Pc) is proved to be comparable efficient in producing energy‐rich oxygen in photo‐ and thermo‐catalytic oxidation and receives massive attention .…”
Section: Introductionmentioning
confidence: 99%
“…This method has been successfully used in cases involving transition metal complexes. [30][31][32] The spin state of the Fe III isomers was stated as high-spin, ground state 6 S, according to the EPR data. The calculations were carried out on a 2.6 GHz Athlon PC, with 1 GB RAM and 40 Gb HD, under the Windows 2000 operational system.…”
Section: Theoretical Calculationsmentioning
confidence: 99%